Gender equality: a perspective of accounting academia in rural area - Noviriani, Eliza; Zurmansyah, Ee (JAS (Jurnal Akuntansi Syariah), 2025)
Purpose – The study aims to answer the question, "How does the gender equality portrait of accounting academics in rural areas?". Method – This research, using gender transcendental phenomenology, encompasses four phases of convergence, namely epoche, reduction of phenomena, imaginative variation, and synthesis between meaning and essence. The primary source of research data, in the form of statements and gestures, was obtained through observation and in-depth interviews. Interviews were conducted with 8 female accountants in academia informants who work and study. Findings – The research showed that gender equality has not realized its specificity for female accountants in academia in the accounting education environment at rural colleges. The "voice" of female accountant academia is divided into two sections: women who feel gender equality and women who experience gender discrimination in the organizational environment. Implications – The theoretical implication of this research is to add to the study of gender equality in the accounting environment, especially for accounting educators and students in rural areas. The practical implications of this research are that the environment should be more sensitive so that this phenomenon does not become more cultural and restrict the movement of glass glasses to work.